Optimization of Growth and Production of Docosahexaenoic Acid by Schizochytrium limacinum BR2.1.2 Using Plackett-Burman Design and Central Composite Design with Response Surface Methodology - Kawsakul, Lalida; Yongmanitchai , Wichien; Chonudomkul, Duenrut (Agriculture and Natural Resources, 2012)
Culture conditions to maximize growth and the production of docosahexaenoic acid (DHA) by Schizochytrium limacinum BR2.1.2 were optimized using two statistical experimental designs. Three critical factors—temperature, glycerol concentration and peptone concentration—for biomass and DHA production were pre-evaluated by the Plackett-Burman design using low and high levels of the three variables. Low temperature, high glycerol and high peptone concentrations signiﬁ cantly inﬂ uenced both determined parameters. A central composite design and response surface plots were used to optimize the proved signiﬁ cant factors and to generate maximum biomass and DHA production. A second order polynomial equation was generated for dried cell weight (DCW) as YDCW = -83.17811 + 7.77533X1 + 22.49818X2 - 32.53142X3 - 0.12375X1X2 + 0.73850X1X3 + 5.41750X2X3 - 0.20343X12 - 1.95541X22 - 9.21053X32 and that for DHA as YDHA = -21.51223 + 1.32761X1 + 5.27758X2 - 4.69083X3 - 0.01150X1X2 + 0.15400X1X3 + 0.65500X2X3 - 0.036655X12 - 0.45401X22 - 1.51840X32. Five levels of each factor at -1.68, -1, 0, +1 and +1.68 were tested in 17 experiments to validate both models. The P-values were less than 0.05 suggesting that the models were acceptable at this level of signiﬁ cance. The optimal values for temperature, glycerol and peptone concentrations were 18.9 °C, 6.1% and 0.7%, respectively, and yielded 48.31 g⋅L-1 of DCW and 5.34 g⋅L-1 of DHA. Veriﬁ cation of the optimal conditions showed that deviations of DCW and DHA from the experimental data and predicted values were 3–5% and less than 2%, respectively, suggesting that the experimental designs used in this work were effective for growth and DHA production.